Radiofrequency Ablation for Early Superficial Flat Esophageal Squamous Cell Neoplasia: A Comprehensive Review - Siyu Lei; Sachin Mulmi Shrestha; Ruihua Shi (Gastroenterology Research and Practice)
Esophageal squamous cell carcinoma comprises the majority of esophageal carcinoma in the Eastern Asia. The need of early detection of precancerous neoplastic lesions and cancer has been necessitated due to the probability of progression to the advanced stage and its poor prognosis. In recent times, many endoscopic modalities have come into practice for early detection and treatment. Endoscopic radiofrequency ablation (RFA) has been recommended as an efficient therapy in treating the dysplastic mucosa in Barrett’s esophagus (BE). Its potential in reversing neoplastic lesions in squamous epithelium has been gradually explored. This article is aimed at reviewing the current evidence regarding the use of RFA on esophageal squamous cell neoplasia.